2013
DOI: 10.1111/ajo.12081
|View full text |Cite
|
Sign up to set email alerts
|

Lactate study using umbilical cord blood: Agreement between Lactate Pro hand-held devices with blood gas analyser and evaluation of lactate stability over time

Abstract: Lactate Pro devices have a significant difference, but when used in clinical practice on cord blood after delivery, this is unlikely to be meaningful. In intrapartum fetal surveillance, a systematic overestimation might lead to unnecessary intervention. It is possible to retrospectively predict the likely level of lactate at birth in delayed cord samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The limits of agreement were validated in a study by Tanner et al 2010 where they were ±2.1 mmol/L [33]. Our previous study showed there were good levels of agreement at low lactate levels in elective Caesarean sections [10]. The between-run coefficient of variation was 3% -5% [8,35] and may be as high as 8.4% in our study, which related to neonates at risk of birth hypoxia.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The limits of agreement were validated in a study by Tanner et al 2010 where they were ±2.1 mmol/L [33]. Our previous study showed there were good levels of agreement at low lactate levels in elective Caesarean sections [10]. The between-run coefficient of variation was 3% -5% [8,35] and may be as high as 8.4% in our study, which related to neonates at risk of birth hypoxia.…”
Section: Discussionsupporting
confidence: 77%
“…However their study did not include samples with lactate concentration high enough to detect the proportional negative bias. In the first part of the study, we found insignificant differences between Lactate Pro and blood gas analyser at low lactate values [10]. Although the manufacturer's specifications indicate Lactate Pro measures lactate concentrations in whole blood between 0.8 and 23 mmol/L, few studies have explored its accuracy at such high lactate levels.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Alternatively, lactate has repeatedly been shown to correlate with umbilical cord pH and to have reasonable accuracy in predicting poor neonatal outcome. [28][29][30][31][32][33][34][35][36][37][38][39] Moreover, it can be measured using a hand-held meter with as little as 5 ll of blood. 30,40 This review aims to synthesise evidence on the diagnostic test accuracy of umbilical cord lactate in measuring acidosis and predicting poor neonatal outcome by comparing umbilical cord lactate with other assessments of acidosis in the immediate newborn and by assessing the ability of umbilical cord lactate to predict neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%